School Leadership and Management: the Head teacher’s Role in Enhancing Learner Academic Performance - Shrestha, Chandra Bahadur; Basnyat, Samjhana (Journal of Business and Social Sciences, 2024)
The leadership and management of schools play an essential role in determining students’ academic progress. The head teacher or school principal is one of the most important stakeholders in education since they are responsible for establishing an encouraging learning environment, executing policies, and making sure that the curriculum is implemented smoothly. This article examines how educational institution management and leadership perceive the head teacher’s contribution to students’ academic success. In Nepal’s educational system, student performance and school leadership remain significant concerns. From a perspective of school management and leadership, we explore the relationship between student performance and school leadership. The opposite characteristics of weak learner performance on the school system or the quality of education are emphasized, even if the causes are just as diverse as the nation itself. As a result, in relation to the leadership of secondary school head teachers, we examined student performance and school leadership. The empirical support for this paper came from the experiences of head teachers. The purposive sampling strategy was used to select participants and in-depth interview was conducted to dig out the information for this study. Four head teachers/principals from four secondary schools in the sindhupalchok district in the Bagmati province, Nepal, were selected as participants in the study. The results show that by performing effective leadership and creating a favorable learning atmosphere, a head teacher’s leadership significantly influences academic achievement. Students’ overall achievement is determined by their willingness to collaborate with stakeholders, use strategic management, and respond to new educational challenges.